2007
DOI: 10.1597/06-071.1
|View full text |Cite
|
Sign up to set email alerts
|

Moebius Syndrome: Measures of Observer Intelligibility with versus without Visual Cues in Bilateral Facial Paralysis

Abstract: The compensatory substitutional placements for phonemes produced by MoS speakers may detract from the intelligibility of speech. This is similar to the McGurk-MacDonald effect, whereby an illusory auditory signal is perceived when visual information from lip movements does not match the auditory information from speech. It also suggests that observers use contextual clues, more than the acoustic signal alone, to arrive at the accurate recognition of the message of the speakers with MoS. Therefore, speakers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Second, does the vowel intelligibility of a speaker presenting with micrognathia and aglossia and subsequent compensatory strategies alter with and without visual cues? This question was posed because past studies have suggested that compensatory placements for difficult phonemes produced by dysarthric speakers may actually detract from the intelligibility of speech (De Feo & Schaefer, 1983; Von Berg, McColl, & Brancamp, 2007). Third, do acoustic analyses of target vowels agree with listener perceptions of vowels?…”
Section: Introductionmentioning
confidence: 99%
“…Second, does the vowel intelligibility of a speaker presenting with micrognathia and aglossia and subsequent compensatory strategies alter with and without visual cues? This question was posed because past studies have suggested that compensatory placements for difficult phonemes produced by dysarthric speakers may actually detract from the intelligibility of speech (De Feo & Schaefer, 1983; Von Berg, McColl, & Brancamp, 2007). Third, do acoustic analyses of target vowels agree with listener perceptions of vowels?…”
Section: Introductionmentioning
confidence: 99%
“…The most common complaint among mothers, after the absence of facial movements, referred to feeding and speech 2 12 13 ; however, problems as understanding language 16 and changes in neurologic examinations, such as calcifications and vascular changes, 10 17 were also discussed. The occurrence on the difficulty of understanding language 16 does not seem to be frequent; however, in our sample we found 33.3% of mothers who complained about this in their children.…”
Section: Discussionmentioning
confidence: 99%
“…Only 5 (27.8%) showed the expected changes of the disease, such the realization of bilabial consonants articulation at other places that not lips and difficulty achieving the apical tongue sounds, as mentioned by other authors. 12 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more standardized approach is therefore crucial, something speech synthesis and animated virtual characters can provide. It has long been known that a wide variety of stimuli can induce McGurk effects, including artificial computer-generated faces 22 , speakers with paralyzed facial muscles 23 , 24 , point-light speech 25 or by occluding part of the face, leaving only the mouth 26 . This suggests that minimal cues are required for a human listener to perceive synthetic audio-visual speech as natural, yet applications to speech perception research remain anecdotal.…”
Section: Introductionmentioning
confidence: 99%